BIOLOGY OF PSETTODES ERUMEI (SCHNEIDER, 1801) AND PSEUDORHOMBUS ARSIUS (HAMILTON, 1822) FROM THE NORTHERN ARABIAN SEA - Hussain, Syed Makhdoom (Indian Journal of Fisheries, 2011)
The flatfishes (Pleuronectiformes) are represented by four families and 28 spedes along Sind and Makran coasts (northern Arabian Sea). Psetlodes erumei and Pseudorhombus arsius contribute major portion of the flatfishes caught from these coasts. The two spedes are distributed in coastal waters, shelf area and off shore waters. P. arsius migrates into aedcs and estuaries. The analysis of length and weight relationship showed isometric growth in both spedes. Studies on food contents revealed higher percentage of invertebrate in juvenile fishes and as fishes grow they change over to fish as major food. Dial difference in feeding habit is also noted in two spedes. Spawning seems to occur from March to May, before onset of monsoon in P. erumei and after monsoon, September - November in P. arsius